Uptake and transformation of phenols by duckweed (Lemna gibba) - Fujisawa, Takuo; Katagi, Toshiyuki; Ichise-Shibuya, Keiko (Journal of Pesticide Science, 2010)
Uptake and transformation of phenol and its five derivatives each labeled with 14C were examined in duckweed (Lemna gibba). A kinetic analysis on uptake and metabolic transformation was conducted using the assumed compartments. Positive correlation was observed between log P and the logarithm value of relative uptake rate constant with respect to phenol, and an even higher correlation was obtained against the physico-chemical index, EffTox, where the undissociated fraction of phenol was incorporated. No significant correlation was observed between any of the electronic parameters of the phenol derivatives and the transformation rate. These analyses showed that the uptake of phenols by duckweed is mainly controlled by the hydrophobic profile of the undissociated form. For the metabolic profile, the glycoside conjugate was detected as a typical major metabolite for all phenols and the glutathione conjugate as a unique metabolite for 4-chlorophenol.